Firm Value Ditinjau dari: Aspek Environmental, Social, Governance (ESG) dan Kontroversinya - Adelina Citradewi; Nasyiyatul Laili (Prodi Akuntansi Syariah UIN Sulthan Thaha Saifuddin Jambi, 2025)
This research aims to investigate the influence of environmental, social, governance (ESG) disclosure and its controversy on company value. The population of this research is 84 food and beverage subsector companies listed on the Indonesia Stock Exchange (BEI) in 2022. The sample was selected using a purposive sampling technique and obtained a sample of 55 companies. The technical analysis involves the use of multiple linear regression methods, and the process will be carried out with the help of the Statistical Package for the Social Sciences (SPSS) application through the stages of descriptive statistical analysis and classical assumption tests (normality test, multicollinearity test and heteroscedasticity test). The results of this research show that Environmental disclosure does not have a significant influence on firm value, social disclosure has a significant influence on firm value, governance disclosure has a significant influence on firm value, and ESG controversy does not have a significant influence on firm value